Síntese de nanopartículas de Ni em matriz de carvão ativado para a adsorção de azul de metileno - Silva, Wanderson de Souza e (2016)
The objective of this work was the synthesis of metallic nanoparticles of nickel in activated carbonmatrix for the adsorption of the methylene blue dye. For this, the activated carbon, originating from the babassu endocarp, was synthesized through the physical activation method and later used as a stabilizer in the synthesis of nickel metal nanoparticles. Synthesis conditions of the nanoparticles were tested, varying the pH and percentage of nickel used. The obtained materials were characterized by techniques of textural analysis, thermogravimetry, atomic absorption, X-ray diffraction, scanning and transmission electron microscopy and measurement of their magnetic properties, and later used in adsorption tests of methylene blue in aqueous solution.Whose efficiency was evaluated by electronic absorption in the ultraviolet-visible region. The synthesized materials had nickel contents of 8.0, 22.7 and 28.9% for the samples prepared at pH7 and 12.8, 23.4 and 27.4% at pH 12. All the samples presented good microporosity and specific surface areas varying from 500 to 850 m2g-1. They also showhigh thermal stability that grows according to the increase of the nickel content. Moreover, the SEM and TEM microscopies showed that the particles are homogeneously dispersed on the surface of the carbonaceous matrix and have a spherical morphology and approximate size of 100 nm. The XRDs show that there are two crystalline phases, one of nickel oxide and the other of metallic nickel and both have a cubic face center arrangement. In addition the measured magnetic properties for the samples prepared in pH12 showed that the material presents ferromagnetic characteristics due to metallic nickel. Finally, the adsorption tests showed that the pure coal sample obtained the highest efficiency in the removal of methylene blue, about2.7 g L-1 of adsorbate per 1.0 g of adsorbent, and the 8.0% -pH7 sample had the second best efficiency with removal of 2.5 g L-1 of adsorbate per 1.0 g of Adsorbent.